Can we benchmark the contribution of research and development investment to growth and competitiveness? - Lena Tsipouri (Science and Public Policy, 2001)
This paper suggests that there is no universal model we can use to quantify the impact of R&D on growth and competitiveness. The design and effectiveness of policies are crucial in this relationship and their effects may be anything from a spectacular success to total misallocation of resources. Selected variables are suggested for benchmarking, such as business R&D, a good share of new-technology based (small) firms and bigger companies, the education and mobility of the labour force and the creation of effective intermediaries that facilitate interaction, as well as a process of restructuring. However, dangers are also associated with such a benchmarking approach, if recommendations neglect path dependencies and apparently best practices are transferred without adaptation.